Development and modeling of a device for strengthening the channels of gun barrels by the method of vibration-centrifugal processing - V. I. Topchii; I. S. Aftanasiv; I. G. Svidrak (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Ґжицького. Серія: Харчові технології, 2019)
The paper proposes a fundamentally new method of vibration-centrifugal hardening of internal cylindrical surfaces of long-length steel parts, in particular artillery guns, belonging to a group of methods of surface plastic deformation, and is characterized by providing a significant level of energy for deformation of the material being processed. Artillery cannons, along with a system for targeting shooting guns, are perhaps the most responsible component, which not only provides range and accuracy of the aiming shot, but also regulates the durability of the gun in general. During each of the gun shots, the surface layers of the metal of the channel of its trunk are exposed to the destructive effects of high (up to 10000 °C) temperatures, the chemical action of powder gases, excessive pressures and mechanical wear on the movement of the shell. This leads to the destruction of the structure, strength and density of the metal surface layers, its burning and wear, which in the rest, leads to violations of the geometry of the working surface of the trunk channel. Violation of the geometry of the working surface of the channel of the gun barrel negatively affects the range, and most importantly, the precision of gunfire and other precision related tactical and technical characteristics of gun armament. Excessively worn internal working surface of the canal of the trunk of repair and restoration is practically not subject. This determines the availability of such characteristics for cannon weaponry as the permissible number of gunfire shots, which to a certain extent limits the duration of the effective use of guns. A rather common practice in mechanical engineering is that when the strength characteristics and capabilities of the materials used are practically exhausted, designers and developers draw their views on the technological capabilities to improve the operational properties of parts and units. Not the last position in their list is the reinforcing operations of the surface layers of the material of the details by various methods of surface plastic deformation, widely known in the literary primary sources under the acronym “PPE methods”. The common advantage of the best of a fairly wide variety of varieties (rolling, rolling, smoothing, blasting and vibrating processing, etc.) is that, without substituting the part for energy-intensive high-temperature heating, the strength characteristics and performance properties of the most loaded surface layers of the material of parts are improved. Accordingly, the use in manufacturing processes of the details of PPD methods helps to increase their reliability and longevity. The developed design of the reinforcement on the basis of the proposed method of vibration-centrifugal hardening treatment is used to strengthen the internal cylindrical channels of the trunk of large-caliber artillery cannons. The reinforcement is simple in structure, energy-saving, does not provide for the maintenance of highly skilled service personnel. The solid-state model of the device for the vibration-centrifugal hardening of the internal cylindrical surfaces of steel parts has been created